2013
DOI: 10.1037/a0031442
|View full text |Cite
|
Sign up to set email alerts
|

Depressive behavior and activation of the orexin/hypocretin system.

Abstract: The orexin/hypocretin peptide signaling system plays a neuromodulatory role in motivation and stress; two critical components of depression. Although work has been done to identify links between orexin and depression, few specific neuroanatomical associations have been made. These studies have not investigated the relationship between orexin and orexin receptor expression in specific brain regions associated with this disorder. To address this, we examined immobility during the forced swim test (FST) in mice, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
47
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(51 citation statements)
references
References 50 publications
2
47
1
1
Order By: Relevance
“…The intensity gradient for anxious behavior was modifiable by a variety of neuromodulatory systems, which include CRF, NPS, NE, as well as Orx and 5-HT, known to modify anxious behavior and synergistically interact within the appropriate circuits (Arendt et al, 2014; Arendt et al, 2013; Cannella et al, 2013; Jungling et al, 2008; Li et al, 2015; Orsini and Maren, 2012; Smith et al, 2014). The results of experiments utilizing the SAM apparatus suggest that in addition to Pavlovian fear conditioning and decision-making (Smith et al, 2014), this model is an effective way to examine the escalation of anxious behavior as environmentally and socially relevant contextual events amplify the intensity of emotional response along a gradient of anxiety (Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The intensity gradient for anxious behavior was modifiable by a variety of neuromodulatory systems, which include CRF, NPS, NE, as well as Orx and 5-HT, known to modify anxious behavior and synergistically interact within the appropriate circuits (Arendt et al, 2014; Arendt et al, 2013; Cannella et al, 2013; Jungling et al, 2008; Li et al, 2015; Orsini and Maren, 2012; Smith et al, 2014). The results of experiments utilizing the SAM apparatus suggest that in addition to Pavlovian fear conditioning and decision-making (Smith et al, 2014), this model is an effective way to examine the escalation of anxious behavior as environmentally and socially relevant contextual events amplify the intensity of emotional response along a gradient of anxiety (Figure 1C).…”
Section: Discussionmentioning
confidence: 99%
“…The intra-amygdalar fear/anxiety circuitry includes a glutamatergic pyramidal circuit (lateral = LA, basolateral = BLA) modified by GABAergic modulation and output (BLA, intercalated, CeA), both additionally modified by CRF, orexin (Orx), NPS, norepinephrine (NE), and serotonin (5-HT). There is strong evidence for modification of anxious behavior, and synergistic cross-talk among transmitter and neuromodulatory elements in this circuit (Arendt et al, 2014; Arendt et al, 2013; Cannella et al, 2013; Jungling et al, 2008; Li et al, 2015; Orsini and Maren, 2012; Smith et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…OXergic cells project to many brain regions that are involved in regulating mood and anxiety (Peyron et al, 1998), and where the expression of OX1R has been confirmed in nocturnal laboratory rats (Trivedi et al, 1998, Lu et al, 2000, Hervieu et al, 2001, Sunter et al, 2001). The involvement of the OXA-OX1R pathway in these sites has been assessed in various animal models of depression (Feng et al, 2007, Feng et al, 2008, Nocjar et al, 2012, Arendt et al, 2013). For example, in a social defeat model, reduced OXA levels were found in VTA and mPFC in defeated animals compared to undefeated controls (Nocjar et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…A Leu72Met polymorphism in the ghrelin gene coding region associates with depression (Nakashima et al, 2008), and elevated ghrelin levels have been found in patients with treatment-resistant depression (Ishitobi et al, 2012), suggesting that ghrelin may be a useful indicator of treatment efficacy. In addition, the orexin system, including the expression of orexin and its receptors (Ox1R and Ox2R) has been implicated in the expression of both maternal care (D'Anna and Gammie, 2006) and depressive behavior and pathophysiology (Arendt et al, 2013; Nollet and Leman, 2013). The clinical and rodent studies indicate that ghrelin and orexin may mediate the depressed maternal care in dams exposed to ECSS.…”
Section: Introductionmentioning
confidence: 99%